The microbiome in adult acute appendicitis. (4th August 2022) - Lee, Mei Sze; Sulit, Arielle; Frizelle, Frank; Purcell, Rachel
Abstract: Acute appendicitis is a common acute surgical emergency; however, the pathogenesis of adult appendicitis remains poorly understood. The microbiome is increasingly thought to play a key role in inflammatory disease of the bowel and similarly, may play a role in appendicitis. This study aimed to characterise the microbiome of adult acute appendicitis in a prospective cohort. We recruited 60 adults with acute appendicitis and 20 healthy controls. Rectal swabs were taken from each patient. After DNA extraction, 16S rRNA amplicon sequencing was carried out for analysis of diversity and taxonomic abundance. Phylogenetic sequencing of the samples indicated that there is a difference between the microbial composition of those with acute appendicitis and healthy controls, with a statistically significant decrease in alpha diversity in rectal swabs of appendicitis patients compared to healthy controls. At the genus level, we saw an increased abundance of potential pathogens, for example, Parvimonas and Acinetobacter, and a decrease in commensal taxa such as Faecalibacterium, Blautia and Lachnospiraceae in appendicitis patients compared to healthy controls. There was a reduction in diversity and loss of commensals in the microbiome of those with acute appendicitis, which may play a role in the cascade leading to acute appendicitis or the result of this.